Synthesis and biotransformation of diarylpentadienones - Alabi, Zaccheaus Oluwatayo (Universidade Federal de São Carlos, 2019)
SYNTHESIS AND BIOTRANSFORMATION OF DIARYLPENTADIENONES. Naturally-occuring compounds containing bis-aryl moiety are important components of fine chemicals required by pharmaceutical, agrochemical and flavor industries. These compounds have inspired the synthesis of several of their analogs such as the diarylpentadienones. These synthetic analogs possess equal or better potential compared to their lead compounds. As part of the ongoing efforts in our laboratory to enlarge the diarylpentadienones library, we synthesized some monoarylidenes and diarylpentadienones (compounds 2, 4, 5, 6) and biotransformed them and some others obtained from the previous works in our laboratory (compounds 7, 8 and 9) using Penicillium brasilianum and Saccharomyces cerevisiae to modify them and enlarge their library. In our finding, the resting cells of P. brasilianum reduced monoarylidene 2 to 10 and further oxidized it to 11 in a Baeyer-Villiger-like manner. However, no biotransformation product was detected when diarylpentadinones 4, 5, 7 and 8 were fed into the fungi. Also, baker’s yeast Saccharomyces cerevisiae reduced 9 to 10 and 11 in a regioselective manner. Further investigation into why P. brasilianum was not able to reduce and/or oxidized diarylpentadienones used must be carried out.

SÍNTESIS Y BIOTRANSFORMACIÓN DE DIARYLPENTADIENONES. Los compuestos naturales que contienen el resto bis-arilo son componentes importantes de productos químicos finos requeridos por las industrias farmacéutica, agroquímica y de sabor. Estos compuestos han inspirado la síntesis de varios de sus análogos, como las diarilpentadienonas. Estos análogos sintéticos poseen un potencial igual o mejor en comparación con sus compuestos principales. Como parte de los esfuerzos en curso en nuestro laboratorio para ampliar la biblioteca de diarilpentadienonas, sintetizamos algunos monoarilidenos y diarilpentadienonas (compuestos 2, 4, 5, 6) y los biotransformamos y otros obtuvimos de los trabajos anteriores en nuestro laboratorio (compuestos 7, 8 y 9) usar Penicillium brasilianum y Saccharomyces cerevisiae para modificarlos y ampliar su biblioteca. En nuestro hallazgo, las células en reposo de P. brasilianum redujeron el monoarilideno 2 a 10 y lo oxidaron aún más a 11 de una manera similar a la de Baeyer-Villiger. Sin embargo, no se detectó ningún producto de biotransformación cuando las diarilpentadinonas 4, 5, 7 y 8 se alimentaron a los hongos. Además, la levadura de panadería Saccharomyces cerevisiae se redujo de 9 a 10 y 11 de manera regioselectiva. Debe llevarse a cabo una investigación adicional sobre por qué P. brasilianum no pudo reducir y / o utilizar diarilpentadienonas oxidadas.

SYNTHÈSE ET BIOTRANSFORMATION DE DIARYLPENTADIENONES. Les composés naturels contenant une partie bis-aryle sont des composants importants des produits chimiques fins requis par les industries pharmaceutique, agrochimique et des arômes. Ces composés ont inspiré la synthèse de plusieurs de leurs analogues tels que les diarylpentadiénones. Ces analogues synthétiques possèdent un potentiel égal ou meilleur par rapport à leurs composés de plomb. Dans le cadre des efforts en cours dans notre laboratoire pour agrandir la bibliothèque de diarylpentadiénones, nous avons synthétisé quelques monoarylidènes et diarylpentadiénones (composés 2, 4, 5, 6) et les avons biotransformés et certains autres obtenus à partir des travaux antérieurs de notre laboratoire (composés 7, 8 et 9) utiliser Penicillium brasilianum et Saccharomyces cerevisiae pour les modifier et agrandir leur bibliothèque. Dans notre découverte, les cellules au repos de P. brasilianum ont réduit le monoarylidène de 2 à 10 et l'oxydé davantage à 11 d'une manière semblable à Baeyer-Villiger. Cependant, aucun produit de biotransformation n'a été détecté lorsque les diarylpentadinones 4, 5, 7 et 8 ont été introduites dans les champignons. De plus, la levure de boulangerie Saccharomyces cerevisiae a réduit de 9 à 10 et 11 de manière régiosélective. Une enquête plus approfondie sur les raisons pour lesquelles P. brasilianum n'a pas pu réduire et / ou les diarylpentadiénones oxydées utilisées doit être menée.

SYNTHESE UND BIOTRANSFORMATION VON DIARYLPENTADIENONEN. Natürlich vorkommende Verbindungen, die Bisarylgruppen enthalten, sind wichtige Bestandteile von Feinchemikalien, die von der pharmazeutischen, agrochemischen und Aromaindustrie benötigt werden. Diese Verbindungen haben die Synthese mehrerer ihrer Analoga wie der Diarylpentadienone angeregt. Diese synthetischen Analoga besitzen im Vergleich zu ihren Leitverbindungen das gleiche oder ein besseres Potenzial. Im Rahmen der laufenden Bemühungen in unserem Labor, die Diarylpentadienonbibliothek zu erweitern, haben wir einige Monoarylidene und Diarylpentadienone (Verbindungen 2, 4, 5, 6) synthetisiert und diese und einige andere, die aus den vorherigen Arbeiten in unserem Labor gewonnen wurden (Verbindungen 7, 8), biotransformiert und 9) Verwenden von Penicillium brasilianum und Saccharomyces cerevisiae, um sie zu modifizieren und ihre Bibliothek zu vergrößern. Nach unserem Befund reduzierten die ruhenden Zellen von P. brasilianum das Monoaryliden 2 auf 10 und oxidierten es auf Baeyer-Villiger-ähnliche Weise weiter zu 11. Bei der Fütterung der Diarylpentadinone 4, 5, 7 und 8 in die Pilze wurde jedoch kein Biotransformationsprodukt nachgewiesen. Auch die Bäckerhefe Saccharomyces cerevisiae reduzierte regioselektiv 9 auf 10 und 11. Weitere Untersuchungen, warum P. brasilianum verwendete Diarylpentadienone nicht reduzieren und / oder oxidieren konnte, müssen durchgeführt werden.

SINTESI E BIOTRANSFORMAZIONE DEI DIARIOPENTADIENONI. I composti naturali contenenti la porzione bis-arilica sono componenti importanti delle sostanze chimiche fini richieste dalle industrie farmaceutiche, agrochimiche e aromatiche. Questi composti hanno ispirato la sintesi di molti dei loro analoghi come i diarilpentadienoni. Questi analoghi sintetici possiedono un potenziale uguale o migliore rispetto ai loro composti di piombo. Come parte degli sforzi in corso nel nostro laboratorio per ampliare la biblioteca di diarylpentadienones, abbiamo sintetizzato alcuni monoarilidi e diarylpentadienones (composti 2, 4, 5, 6) e li abbiamo trasformati biotrasformati e alcuni altri ottenuti dai precedenti lavori nel nostro laboratorio (composti 7, 8 e 9) usare Penicillium brasilianum e Saccharomyces cerevisiae per modificarli e ampliare la loro biblioteca. Nella nostra scoperta, le cellule a riposo di P. brasilianum hanno ridotto il monoarylidene da 2 a 10 e l'hanno ulteriormente ossidato a 11 in modo simile a Baeyer-Villiger. Tuttavia, nessun prodotto di biotrasformazione è stato rilevato quando i diarilpentadinoni 4, 5, 7 e 8 sono stati alimentati nei funghi. Inoltre, il lievito per panificazione Saccharomyces cerevisiae ha ridotto da 9 a 10 e 11 in maniera regioselettiva. Devono essere condotte ulteriori indagini sul perché P. brasilianum non è stato in grado di ridurre e / o ossidare i diarilpentadienoni utilizzati.

二芳基二烯酮的合成和生物转化。含有双芳基部分的天然存在的化合物是制药，农业化学和调味品工业所需的精细化学品的重要成分。这些化合物激发了其一些类似物如二芳基戊二烯酮的合成。与它们的先导化合物相比，这些合成类似物具有相同或更好的潜力。作为我们实验室为扩大二芳基戊二烯酮库所做的不断努力的一部分，我们合成了一些单芳基芳烃和二芳基戊二烯酮（化合物2、4、5、6），并对它们进行了生物转化，以及从实验室以前的工作中获得的其他化合物（化合物7、8） 9）使用巴西青霉和酿酒酵母对其进行修饰并扩大其文库。在我们的发现中，巴西假单胞菌的静止细胞将单亚芳基2还原为10，然后以类似于Baeyer-Villiger的方式将其氧化为11。然而，当将二芳基戊二酮4、5、7和8进料到真菌中时，没有检测到生物转化产物。此外，面包酵母啤酒酵母以区域选择性方式将9降低为10和11。必须进一步调查为什么巴西布鲁氏菌不能还原和/或氧化所用的二芳基戊二烯酮。

Синтез и биотрансформация диарилпентадиенов. Встречающиеся в природе соединения, содержащие бисарильную часть, являются важными компонентами тонких химических веществ, необходимых для фармацевтической, агрохимической и вкусовой промышленности. Эти соединения вдохновили синтез некоторых из их аналогов, таких как диарилпентадиеноны. Эти синтетические аналоги обладают равным или лучшим потенциалом по сравнению с их соединениями свинца. В рамках продолжающихся в нашей лаборатории усилий по расширению библиотеки диарилпентадиенонов мы синтезировали некоторые моноарилидены и диарилпентадиеноны (соединения 2, 4, 5, 6) и биотрансформировали их, а также некоторые другие, полученные из предыдущих работ в нашей лаборатории (соединения 7, 8 и 9) использование Penicillium brasilianum и Saccharomyces cerevisiae для их модификации и расширения своей библиотеки. В нашем открытии покоящиеся клетки P. brasilianum восстанавливали моноарилиден от 2 до 10 и дополнительно окисляли его до 11 по типу Байера-Филлигера. Однако продукт биотрансформации не был обнаружен при введении диарилпентадинонов 4, 5, 7 и 8 в грибы. Кроме того, пекарские дрожжи Saccharomyces cerevisiae сократили 9-10 и 11 региоселективным образом. Необходимо провести дальнейшее расследование того, почему P. brasilianum не способен восстанавливать и / или использовать окисленные диарилпентадиеноны.
二芳基戊二烯酮的合成和生物转化
ジアリールペンタジエノンの合成と生体内変換
Keywords: Diarylpentadienones; Monoarylidenes; Bis-aryl moiety; Baeyer-Villiger monooxygenases; Baeyer-Villiger oxidation; Carbon-carbon double bond reduction; Old yellow enzymes; Chromatography; Nuclear magnetic resonance; Diarlpentadienonas; Monoarilidenos; Parte bis-aril; Monooxigenases de Baeyer-Villiger; Oxidação de Baeyer-Villiger; Biocatalisador; Redução de dupla ligação carbono-carbono; Enzimas amarelas antigas; Ressonância magnética nuclear; Cromatografia; Diarylpentadienone; Monoarylidene; Bisarylreste; Baeyer-Villiger-Monooxygenasen; Baeyer-Villiger-Oxidation; Biokatalysator; Kohlenstoff-Kohlenstoff-Doppelbindungsreduktion; Alte gelbe Enzyme; Kernspinresonanz; Chromatographie; Penicillium brasilianum; Saccharomyces cerevisiae; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS